I family business e la successione padre-figlia nella cultura italiana: un caso di studio - Cassia, Lucio; De Massis, Alfredo; Giudici, Federica (Piccola Impresa / Small Business, 2011)
The case-study investigates the succession process characterized by the transition of leadership from father to daughter, focusing on the relationships among the actors involved, the way the succession process takes place and the main issues emerged. The aim is to detect the presence of cultural elements specific to the Italian context that may influence this process. The central role traditionally played by the family in the Italian culture justifies and determines the preponderance of the family business on the lives of family members. This is the reason why the intention of successors to ensure the continuity of the family business is an overwhelming and decisive motivation to join the company; this motivation has driven the successor to take the helm of the firm even if she is a woman entering an industry traditionally reserved to men. The take over of the leadership is even more critical for women, because of the propensity of parents to educate sons and daughters in different ways. The emerged empirical evidence seems therefore to suggest that in the Italian culture there are activities and industries best suited to one sex more than to the other, and there is diffused conviction that the business approach, the leadership style and the skills of an individual depend not only on his or her own individuality, but also, significantly, on his or her gender. In particular, according to the exploratory findings of this case-study, it seems that women pay more attention to relational aspects and show high propensity to delegate tasks and activities, while men are characterized by a more centralized and authoritarian leadership style.